The Role of Information and Communications Technology in Promoting Services Marketing Practices in Organizations - الشريف , أحمد (Dirasat in Economics and Business, 2017)
In the marketing field, information and communications technology (ICT) and associated applications (such as E-commerce, E-marketing ) have changed the form and manner of marketing practices as well as the ways in which organizations, especially service ones, deal with their customers. So, this research was intended to answer the following question: What is the role of ICT in promoting services marketing practices in organizations? To answer the previous question, and based on the theoretical nature of the research, the concepts and related research contributions were reviewed and analyzed in this regard. The research concluded some implications and provided set of recommendations that might guarantee and advanced pace of use ICT in promoting services marketing practices in organizations.